(untitled) (Physical Education, Health and Social Sciences, 2025)
Service exports play a big role in bringing in foreign exchange and helping developing countries diversify their economies. This study investigated how Pakistan’s digital economy shaped its service exports from 1993 to 2023. The Autoregressive Distributed Lag (ARDL) model had been used to build a new Digital Economy Development Index (DEDI), using the entropy weighting method, to get a full picture of digital progress. There observed a strong, positive long-term link between the DEDI and service exports. Financial depth has a negative long-run effect. The Real Effective Exchange Rate (REER) has a positive short-term influence, that showed that currency shifts can help service producers get the imported inputs. The study also checked for cointegration and model stability. Digital infrastructure pushes the sector forward, but a poorly functioning financial system holds it back. So, policymakers need a two-pronged approach: invest heavily in digital infrastructure, training, and connectivity, and at the same time, overhaul the financial sector to make credit more accessible for service-based SMEs and freelancers.